Compression-compression fatigue behavior of CuZr-based bulk metallic glass composite containing B2 phase. (June 2017) - Wei, R.; Chen, L.B.; Li, H.P.; Li, F.S.
Abstract: The fatigue behavior of Cu47.5 Zr48 Al4 Co0.5 bulk metallic glass composite (BMGC) containing B2 phase was investigated under uniaxial compression-compression loading modes at 80 Hz with a 0.1 R ratio. The Cu46.5 Zr46.5 Al7 bulk metallic glass (BMG) was selected as a reference materials. It was found that the BMGC exhibits a lower fatigue limit (1300 MPa) than that of its reference BMG (1500 MPa), which is due to the lower yield strength of the BMGC. The fatigue limit is characterized by the stress range, σr =(σmax -σmin ), where σmin and σmax are the applied minimum and maximum stresses, respectively. However, the fatigue ratio (the maximum stress range/yield strength) of the BMGC is higher than that of the BMG, because the "blocking effect" and "martensitic transformation effect" of B2 phase can effectively impede the propagation of fatigue crack and enhance the yield strength of the BMGC. Briefly, B2 phases can obviously improve the fatigue ratio of the CuZr-based BMGCs and thus improve its fatigue behavior, though it can not improve its fatigue limit. Highlights: Compression–compression fatigue behavior of Cu47.5 Zr48 Al4 Co0.5 BMGC was investigated. Martensitic transformation occurs in B2 phases, which hinder the fatigue crack propagation. The BMGC possess lower fatigue limit but higher fatigue ratio than that of the BMG. The fatigue mechanism of BMGC was discussed.